2017
DOI: 10.1037/ccp0000133
|View full text |Cite
|
Sign up to set email alerts
|

Child STEPs in California: A cluster randomized effectiveness trial comparing modular treatment with community implemented treatment for youth with anxiety, depression, conduct problems, or traumatic stress.

Abstract: These results extend prior findings, supporting the effectiveness and efficiency of a modular, multifocus approach that incorporates monitoring and feedback relative to community implementation of evidence-based treatments. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 60 publications
4
129
2
Order By: Relevance
“…Of interest, all of these practices were the first skills that providers would have taught to clients, following any engagement and psychoeducation practices, if they were adhering to the default sequences of practices featured in the MATCH-ADTC manual. Such findings are reassuring—not only in that they provide additional support for providers’ frequent use of EBT practices (e.g., Palinkas et al, 2013; Park et al, 2015), but also in that they suggest that providers are adhering to the sequencing prescribed by the modular EBT (as a portion of youths prematurely terminated from treatment [Chorpita et al, 2016] and thus frequency of practice delivery is likely biased toward practices covered in the early stages of treatment).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Of interest, all of these practices were the first skills that providers would have taught to clients, following any engagement and psychoeducation practices, if they were adhering to the default sequences of practices featured in the MATCH-ADTC manual. Such findings are reassuring—not only in that they provide additional support for providers’ frequent use of EBT practices (e.g., Palinkas et al, 2013; Park et al, 2015), but also in that they suggest that providers are adhering to the sequencing prescribed by the modular EBT (as a portion of youths prematurely terminated from treatment [Chorpita et al, 2016] and thus frequency of practice delivery is likely biased toward practices covered in the early stages of treatment).…”
Section: Discussionmentioning
confidence: 90%
“…Data were collected during the treatment phase of a community-based randomized clinical trial comparing a modular EBT with multiple community-implemented EBTs (e.g., Southam-Gerow et al, 2014) for children and adolescents presenting with problems in the areas of anxiety, depression, or conduct (see Chorpita et al, 2016, for more information). The treatment phase of this trial took place in Los Angeles, CA, from 2010 to 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were selected from the modular EBT condition (MATCH) of the Child STEPs in California study, a randomized clinical trial (RCT) conducted at three large community mental health agencies in urban California (Chorpita et al, 2017). Participants from the usual care condition of the trial were not included in the present study due to the inability to compare these providers’ responses to ELEs with ratings of ELE addressability using MATCH.…”
Section: Methodsmentioning
confidence: 99%
“…Youth were excluded if they had mental health concerns that could not be addressed with MATCH, including intellectual disability, autism, psychosis, recent suicide attempt, severe trauma, and juvenile justice involvement. Additional details and the flow of youth into the study according to CONSORT guidelines are reported in the original outcome paper (Chorpita et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation